2017
DOI: 10.1186/s40798-017-0075-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Concurrent Plyometric Training Versus Submaximal Aerobic Cycling on Rowing Economy, Peak Power, and Performance in Male High School Rowers

Abstract: BackgroundPlyometric training has been shown to increase muscle power, running economy, and performance in athletes. Despite its use by rowing coaches, it is unknown whether plyometrics might improve rowing economy or performance.The purpose was to determine if plyometric training, in conjunction with training on the water, would lead to improved rowing economy and performance.MethodsEighteen male high school rowers were assigned to perform 4 weeks of either plyometric training (PLYO, n = 9) or steady-state cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Numerous studies showed 56,57 that SSC performance can be increased mainly by reactive force capabilities, induced by adequate training (e.g., plyometrics). In the context of plyometric training (SSC related training) in rowing, contradictory research results exist: While one intervention study (n = 18, 4 weeks) revealed rowing-specific performance improvements through plyometric training 28 , another intervention study (9 weeks, n = 24) observed no rowing-specific performance improvements 27 . These contradictory results might be explained by methodological issues: One Study 28 was volume matched but not workload matched and the performance level of the participants (in both studies) 27,28 was very low (500 m time trial mean power was about 45% lower than the performance of the participants in this current study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies showed 56,57 that SSC performance can be increased mainly by reactive force capabilities, induced by adequate training (e.g., plyometrics). In the context of plyometric training (SSC related training) in rowing, contradictory research results exist: While one intervention study (n = 18, 4 weeks) revealed rowing-specific performance improvements through plyometric training 28 , another intervention study (9 weeks, n = 24) observed no rowing-specific performance improvements 27 . These contradictory results might be explained by methodological issues: One Study 28 was volume matched but not workload matched and the performance level of the participants (in both studies) 27,28 was very low (500 m time trial mean power was about 45% lower than the performance of the participants in this current study).…”
Section: Discussionmentioning
confidence: 99%
“…The assumption that the entire muscle tendon complex performs a SSC during this flexion-extension cycle is confirmed by eccentric muscle activity during the late gliding-phase before the start of a new rowing stroke [18][19][20][21][22] . In rowing, jumps are trained over the entire year and thus constitute a central component of the testing and training schedules of rowers [23][24][25][26][27][28] . In this context, fast (such as DJ) and slow SSC movements (such as CMJ) are frequently applied 23,29 .…”
mentioning
confidence: 99%
“…In general, numerous studies showed (Stojanović et al, 2017;Berton et al, 2018) that SSC performance can be increased mainly by reactive force capabilities, induced by adequate training (e.g., plyometrics). In the context of plyometric training in rowing, contradictory research results, however, exist: While one intervention study (n = 18, 4 weeks) revealed rowingspecific performance improvements through plyometric training (Egan-Shuttler et al, 2017), another intervention study (n = 24, 9 weeks) observed no rowing-specific performance improvements (Kramer et al, 1993). These contradictory findings might partly be explained by methodological issues.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise greater flexibility has been related to better performance in swimmers. 8 Current research into PT has demonstrated an improvement in jumping ability in activities including soccer, 9 rowing, 10 handball, 11 and hockey. 12 This is no different in swimmers, but the scientific evidence is controversial and limited.…”
Section: Introductionmentioning
confidence: 99%